Growth response of Douglas fir to the first early and delayed thinning - Dušek David; Novák Jiří (Central European Forestry Journal)
Douglas fir (Pseudotsuga menziesii [Mirb.] Franco) is considered one of the most promising introduced tree species for use in forestry in Central Europe. The formation of vital and stable forest stands with a certain share of Douglas fir (DF) requires the application of appropriate silvicultural measures, such as thinning. The article evaluates the growth response of DF to the initial experimental thinning. Eight stands were analysed on nutrient-rich sites in the three forest vegetation zones (Querceto-Fagetum, Fagetum, Abieto-Fagetum). The analysis includes both stands dominated by DF and stands where DF is only interspersed. The thinning was applied when the dominant tree height ranged from 5 to 20 m. A dominant tree height of 10 m was used as the threshold to define well-timed thinning. The data were analysed using Bayesian hierarchical modelling, and generalized hierarchical models were employed. DF promising trees responded to early thinning with significant acceleration of radial growth, leading to improvements in height-to-diameter ratio (HDR) and crown ratio (CR) parameters. The response of DF promising trees to delayed thinning was negligible. Neither early nor delayed thinning had a detectable effect on height growth of the DF promising trees. The result confirms the necessity of initiating thinning for DF stands at the stage of thickets. The thinning should ideally begin when the dominant tree height is between 4 to 5 meters. At this stage, it is possible to positively influence diameter growth and mitigate the deterioration of individual tree stability as well as the stability of the whole stand.